A peer-influence perspective on compulsive social networking site use: Trait mindfulness as a double-edged sword. (December 2017) - Turel, Ofir; Osatuyi, Babajide
Abstract: There is an increasing concern regarding the emergence of harmful compulsive use patterns among some social networking sites (SNSs) users. Although SNSs are efficient social interaction tools, there is a dearth of research that seeks to understand peer-influence determinants of compulsive SNS use. This study attempts to bridge this gap and tests a model that accounts for the effects of peer-influence mechanisms on compulsive SNS use. Because mindfulness is important for the observation of and cognitive deliberation regarding peer influences, the model also accounts for possible moderating effects of mindfulness. To test this model we conducted a two-wave survey of 155 SNS users from the US. Findings based on hierarchical regression models show that while observed increase in peer SNS use augments compulsive SNS use, social pressure self-efficacy reduces it. Trait mindfulness was found to accentuate these influences and serve as a double-edged sword: it strengthened the inhibiting effect of social pressure self-efficacy on compulsive SNS use, but increased the positive effect of observed peer use increase on compulsive SNS use. Moreover, about 11% of our sample met presumed rudimentary clinical compulsiveness screening criteria. Logistic regression showed that the likelihood of meeting these criteria is reduced with increases in SNS experience and social pressure self-efficacy. These findings can serve as a basis for the development of interventions that target such factors. Highlights: Increase in peer activity on Social Networking Sites (SNS) drives compulsive use. One's ability to fend-off social pressures to use SNS reduces compulsive use. Trait mindfulness is a double-edged sword in the case of compulsive SNS use. It augments the negative effect of social pressure self-efficacy on compulsive use. It enhances the positive effect of increase in peer SNS activity on compulsive use.